Hybridizaton and the theatre practice: an analysis of legends the musical (2025)
Musical theatre basically refers to a kind of theatre practice which relies heavily arts of the theatre like acting, dance and music. It uses these media as a means to communicate certain messages or aesthetic satisfaction for the audience. This research provides a review of the key elements of musical theatre using John Kenrick's approach as well as the interplay of narrative and music with choreography and staging. The study addresses, through performance analysis of Legends the Musical, how its narrative, technical production and use of stage elements resonate more closely with musical theatre traditions. This research also sheds light on the views which place its classification as a musical (rather than operatic) performance. Additionally, the research highlights that modern theatrical productions draw from global and hybridization to establish a new performance mode by mixing in cultural and artistic style. The relevance of Legends the Musical in the Nigerian context is also considered, as well as how it can help to revitalize Nigeria's theatre practices by bringing in bigger audience base and greater commercial viability. Legends the Musical is both entertaining and culturally significant in the way that the interplay of the traditional African deities across the plot represents the socio political challenges facing the continent. The study recommends, therefore, that musical theatre is a viable, dynamic and hybrid art form that can uniquely appeal to and entertain different audiences along the way to reviving the Nigerian theatre culture.